Financial Distress dan Peran Prediktif Rasio-Rasio Keuangan - Gede Dana Pramitha; Desy Wedasari (Juara: Jurnal Riset Akuntansi, 2021)
Distress in financial is a declined financial conditions before bankruptcy or liquidation. Analysis in financial ratio could be use to predict whether companies are facing financial difficuties. The purpose of this study is to examine the relation of financial ratios in predicting financial distress. The sample was 98 manufacturing companies listed for the period of 2016-2018 at Indonesia Stock Exchange. Purposive sampling method to determined sample and analyzed with logistic regression. The results found Current Ratio, Total Asset Turnover and Sales growth variables had no effect while Debt To Total Asset Ratio positively affect and Return on assets has a negative effect in predicting financial distress.